Cybersecurity Behavior as a Reflection of Ḥifẓ al-Māl in Islamic Banking: A Behavioral Model Based on Protection Motivation Theory - Hutagalung, Muhammad Wandisyah R; Siregar, Saparuddin; Furqan, Mhd.; Pulungan, Ismail; Elce, Furkan (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2025)
This study examines psychological determinants of cybersecurity protection behavior among Islamic banking customers by applying Protection Motivation Theory (PMT) within a maqāṣid al-sharīʿah framework. Using a quantitative survey (N = 384) and PLS-SEM, it tests the effects of perceived vulnerability, severity, self-efficacy, response efficacy, response cost, and social influence, as well as the moderating role of cybersecurity education. Results show that vulnerability, severity, response efficacy, and social influence significantly predict protection behavior, while self-efficacy and response cost do not. Cybersecurity education has no significant moderating effect. The model explains 69.6% of the variance, indicating strong explanatory power. The study contributes by linking PMT to Islamic economic principles, particularly ḥifẓ al-māl and amānah. It suggests that Islamic banks need community-based, values-driven cybersecurity education to foster sustainable protective behavior.